Project Management JumpStart. - Heldman, Kim (John Wiley & Sons, Incorporated, 2018)
An informative introduction for those considering a career in project management Project Management JumpStart offers a clear, practical introduction to the complex world of project management, with an entertaining approach based on real-world application. Fully revised to align with a Guide to the Project Management Body of Knowledge -PMBOK Guide©, 6th edition , this book provides an overview of the field followed by an exploration of current best practices. The practical focus facilitates retention by directly linking critical concepts to your everyday work, while the close adherence to PMBOK guidelines makes this book the perfect starting point for those considering certification to earn either PMP or CompTIA Project+ credentials. Project management is a top-five, in-demand skill in today's workplace, and the demand has spread far beyond IT to encompass nearly every industry; any organization that produces goods or services, whether for profit or not, has a vested interest in ensuring that projects are completed on time, on budget, and to the satisfaction of the client--this is the heart of the project management function. Let Kim Heldman, bestselling author of PMP Study Guide and CompTIA Project+ Study Guide , walk you through the basic principles and practices to help you build a strong foundation for further training. Understand current project management methods and practices Explore project management from a practical perspective Delve into illustrative examples that clarify complex issues Test your understanding with challenging study questions Trillions of dollars are invested in various projects around the world each year, and companies have learned that investing in qualified project management professionals pays off in every aspect of the operation. If you're considering a career in project management, Project Management JumpStart provides an excellent introduction to the field and clear direction for your next steps.